From Leadership to Innovation: Transforming Business Performance in Culinary Sector SMEs - Sugeng, Novita Widyastuti; Ingkadijaya, Rahmat; Nurbaeti, Nurbaeti; Asmaniati, Fetty; Riyadi, Agus (Universitas Tanjungpura, 2026)
This study aims to examine the effect of entrepreneurial leadership and network capability on organizational creativity and innovation, with entrepreneur performance as a mediating variable among culinary SMEs in Jakarta. A quantitative approach with an explanatory design was employed to test causal relationships among variables. Data were collected through questionnaires distributed to 500 SME owners or managers using purposive sampling. The research instrument applied a 1–5 Likert scale, and data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that entrepreneurial leadership and network capability significantly influence entrepreneur performance. In addition, entrepreneurial leadership and entrepreneur performance have significant effects on organizational creativity and innovation. However, network capability does not have a direct significant effect on organizational creativity and innovation. Furthermore, entrepreneur performance acts as a mediating variable that strengthens the relationship between entrepreneurial leadership and network capability with organizational creativity and innovation. The study concludes that improving organizational creativity and innovation in SMEs depends on strong entrepreneurial leadership, effective network management, and the ability of entrepreneurs to strategically utilize opportunities and resources.